Sustainable synergy: Valorisation of spent lithium-ion batteries and dry reforming of methane for a circular energy future - Dubois, Franco Ignacio (2025)
From the recovery of Ni, Co, and Mn from Li-ion batteries using the hydrometallurgicaltechnique, two catalysts supported on γ-Al₂O₃ with different metal load concentrations wereprepared. The catalysts were characterized using XRD, SEM, TPR, XPS and BET surface area measurements. These catalysts were studied in the dry reforming of methane reaction at 600°C.The results showed that the solids prepared from a leach solution of lithium-ion batteries exhibit good catalytic activity in the DRM reaction at low temperatures (600°C). The prepared catalysts demonstrated good performance, with conversion rates comparable to those in other studies and an H₂/CO ratio of 0.7-0.8, making them promising for catalytic applications aimed at reducing greenhouse gases and hazardous waste, such as those found in these batteries.